Breed and Gender Interact to Affect the Sale Price of Beef Calves Sold through Video Auctions from 2010 through 2014 - E. D. McCabe; M. E. King; K. E. Fike; K. L. Hill; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2016)
In recent years, the sale prices of beef calves have increased on average, in part due to tighter supply of beef calves and generally strong demand for beef products by consumers. Historically, research has demonstrated beef calf sale price to be influenced by a variety of calf management factors and characteristics. The opportunity to comprehensively evaluate some of these factors amidst recent dynamic changes in the beef industry has been available through analysis of sale prices of beef calves sold as lots via a livestock video auction service. The objective of this study was to quantify the effects of breed, gender, and their potential interaction on sale price of beef calves marketed through video auctions, while adjusting for other factors that significantly influenced price.
Keywords: breed; market; price